Addressing the Global Environmental Crisis: Strategies for Sustainable Development - Subhan Ansori; Ramdan Yusuf (West Science Social and Humanities Studies, 2023)
The global environmental crisis presents an urgent challenge that requires comprehensive strategies for sustainable development. This research employs a bibliometric analysis and VOSviewer visualization to examine the evolving landscape of literature on strategies to address the crisis. The study identifies clusters of research themes, influential authors, and key concepts. Results reveal prominent clusters discussing environmental governance, economic growth, ecological crises, and the role of education in sustainable development. Highly cited publications encompass the triple bottom line concept, sustainable business strategies, and knowledge systems. The analysis underscores the interdisciplinary nature of the field and the need for integrated approaches to achieve ecological, social, and economic sustainability. This research offers insights into current trends and informs future research and policy directions.